Fluorescent Carbon Dots: Fantastic Electroluminescent Materials for Light‐Emitting Diodes - Zhao, Biao (Adv Sci (Weinh), 2021)
Fluorescent carbon dots (CDs) have emerged as fantastic luminescent nanomaterials with significant potentials on account of their unique photoluminescence properties, high stability, and low toxicity. The application of CDs in electroluminescent light‐emitting diodes (LEDs) have aroused much interest in recent years. Herein, the state‐of‐the‐art advances of CD‐based electroluminescent LEDs are summarized, in which CDs act as active emission layer and interface transport layer materials is discussed and highlighted. Besides, the device structure of CD‐based LEDs and preparation methods of CDs are also introduced. Furthermore, the opportunities and challenges for achieving high performance CD‐based electroluminescent LED devices are presented. This review article is expected to stimulate more unprecedented achievements derived from CDs and CD‐based electroluminescent LEDs, thus further promoting their practical applications in future solid‐state lighting and flat‐panel displays.